Parthenogenetic activation of bovine oocytes using single and combined strontium, ionomycin and 6-dimethylaminopurine treatments - Meo, S. C.; Yamazaki, W.; Ferreira, C. R.; Perecin, F.; Saraiva, N. Z.; Leal, C. L. V.; Garcia, J. M. (Cambridge University Press, 2007)
In vitro-matured (IVM) bovine oocytes were activated with single and combined treatments of strontium (S), ionomycin (1) and 6-DMAP (D). Using oocytes IVM for 26 h, we observed that activation altered cell cycle kinetics (faster progression, MIII arrest, or direct transition from MII to pronuclear stage) when compared to in vitro fertilization. The effect of oocyte age on early parthenogenesis was assessed in oocytes IVM for 22, 26 and 30 h. Better results in pronuclear development were obtained in treatments ISD (81.7%) at 22 h; D (66.7%), IS (63.3%), ID (73.3%) and ISD (76.7%) at 26 h; and D (86.7%), IS (85.0%) and ID (78.3%) at 30 h. Higher cleavage occurred on ISD (80.0%) at 22 h; ID (83.3%) and ISD (91.7%) at 26 h; and 1 (86.7%), IS (90.0%), ID (85.0%) and ISD (95.0%) at 30 h. More blastocysts were achieved in ID (25.0%) and ISD (18.3%) at 22h; and in ID at 26h (45.0%) and 30h (50.0%). We also observed that IS allowed higher haploid (77.4%) embryonic development, whilst ID was better for diploid (89.1%) development. It was concluded that association of S and D without I was not effective for blastocyst development; treatments using S were less influenced by oocyte age, but when S was associated with D there was a detrimental effect on aged oocytes; treatment ISD promoted higher activation and cleavage rates in young oocytes and ID protocol was the best for producing blastocysts.
Keywords: Cattle; chromatin; embryonic development; microtubules; oocyte activation